A roadmap for clinical trial design in marginal zone lymphoma. Issue 11 (12th September 2022) - Alderuccio, Juan Pablo; Habermann, Thomas; Kuker, Russ; Moskowitz, Craig H.; Zelenetz, Andrew D.; Lossos, Izidore S.
Abstract : Marginal zone lymphoma (MZL) is commonly underrepresented in clinical trials collectively studying mostly nodal indolent lymphomas.In this manuscript we propose new inclusion and response criteria defined by MZL subtype and disease location for those with extranodal MZL. Progression of disease within 24 months is associated with poor outcomes in MZL and future studies should assess the efficacy of novel agents in this population.